2008
DOI: 10.1002/pola.22945
|View full text |Cite
|
Sign up to set email alerts
|

β‐Hydrogen transfer from poly(methyl methacrylate) propagating radicals to the nitroxide SG1: Analysis of the chain‐end and determination of the rate constant

Abstract: Methyl methacrylate (MMA) was polymerized in bulk at 70 °C in the presence of an alkoxyamine initiator with low dissociation temperature (the so‐called BlocBuilder™) and increasing amounts of free N‐tert‐butyl‐N‐(1‐diethylphosphono‐2,2‐dimethylpropyl) nitroxide (SG1). Low final monomer conversions were reached, indicating a loss in radical activity due to side reactions such as irreversible homoterminations between the propagating radicals and β‐hydrogen transfer (also called disproportionation) from a propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 28 publications
6
126
0
Order By: Relevance
“…3 The polymerization stops at low conversion and highly disperse polymers of uncontrolled molecular weight are obtained. The level of ester group incorporation is controlled, leading to reductions in molecular weight of up to 95% on hydrolysis.…”
mentioning
confidence: 99%
“…3 The polymerization stops at low conversion and highly disperse polymers of uncontrolled molecular weight are obtained. The level of ester group incorporation is controlled, leading to reductions in molecular weight of up to 95% on hydrolysis.…”
mentioning
confidence: 99%
“…Additionally, Dire et al [46] confirmed that the rate constant for β-hydrogen transfer (k βtr ) of methyl methacrylate/SG1 system was three orders of magnitude lower compared to a n-butyl methacrylate/TEMPO system. As a result, SG1-based initiators can be activated at lower temperatures and allow controlled polymerizations of a wider range of monomers, such as methacrylates, compared to TEMPO.…”
Section: Level Of Control Of the Copolymerizations And The Livingnessmentioning
confidence: 62%
“…A nitroxide-controlled homopolymerization of methyl methacryclate (MMA) is not possible due to the degradation of nitroxide by H-abstraction [49]. The SG1-controlled radical copolymerization of MMA and styrene (S) is therefore of particular interest, since Charleux et al [50] demonstrated the possibility of performing a nitroxide-controlled polymerization of methyl methacrylate with a small amount of styrene.…”
Section: Kinetic Modelmentioning
confidence: 99%